Penggunaan Metode Altman Z-score Modifikasi Untuk Memprediksi Kebangkrutan Bank Yang Terdaftar Di Bursa Efek Indonesia - Sagho, Maria Florida; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi; Vol 11 No 3 (2015), 2015)
This research was conducted to predict bankruptcy in banking companies listed in Indonesia Stock Exchange for 2011-2013 with the Altman Z-score modification method. the reseach use a 11 banks that do mergers and acquisitions, namely Mutiara Banks, CIMB  Niaga Banks, Permata Banks, Windu Ketjana International Banks, OCBC NISP Banks, Central Asia Banks, Mandiri Banks, Rakyat Indonesia Banks, Tabungan  Negara Banks, Ekonomi Rahardja Banks, Internasional Indonesia Banks. The analysis techniques  in this research is the Altman Z-score method using 5 ratio, that working capital to total assets ratio (X1), retained earnings to total assets ratio (X2), earnings before interest and taxes to total assets ratio (X3), market value of equity to total debt ratio (X4). The formula of Altman Z-score method to calculate the level of health for the company, that Z-score = 6.56 X1 + X2 + 6.72 3.26 + 1.05 X3 X4. Z-Score indicator to determine the bankruptcy of companies grouped into the healthy category (Z-score> 2.60), gray area (Z-scores between 1.1 and 2.60) and bankrupt (Z-score <1.1). After calculation is concluded that all the banks research from 2011 to 2013 resulted in a Z-Score greater than 2.6, or in other words, the 11 banks is not indicated any symptoms of bankruptcy even reverse all banks surveyed would not be expected to bankruptcy within a period of 1 year.
Keywords: Altman Z-score modification, bankruptcy, prediction